“When We Talk About Compliance, It’s Because We Lived It” - Online Educators’ Roles in Supporting Students with Disabilities - Rice, Mary Frances; Carter, Jr., Richard Allen (Online Learning, 2015)
As participation in online learning grows, so do concerns around the ways in which students with disabilities are served in virtual school programs, both full and part-time. At the crux of this struggle is the way in which federal and state laws (many of which were incepted before online learning existed or gained traction as an educational option) are interpreted by educators and translated into policies at the school level. Further, administrators, special education case managers, and teachers all interpret school level policies and answer to directives from a hierarchy of supervisors. The interpretations of these policies and the understandings educators use to guide their thinking have not been well-researched. In the present study, teachers, special education case managers, school level special education administrators, and regional directors were interviewed about their roles in developing, supporting, and implementing accommodations and other forms of support for students with disabilities in online courses. Findings from this work focus on the role conceptions of various types of educators in virtual schools and the tensions they experience as they work to support each other in positioning students with disabilities for success.